Logical Intelligence and its Relationship to the Sensitivity of Sensory Processing of Students in Distinguished Schools (Journal Of Educational and Psychological Researches, 2023)
AbstractThe research aims to identify the logical intelligence of distinguished students and to identify the extent of the contribution of the fields of logical intelligence to the sensitivity of students' sensory processing in distinguished schools. The research sample consisted of (400) male and female students selected by the stratified random method with the proportional method. The scale that was prepared according to the theoretical framework and the adopted theory was applied after being subject to the psychometric properties of validity and reliability, Logical thinking (observation, interpretation, mathematical and arithmetic operations) contributed to sensory processing. The results showed that distinguished students have a high ability to master logical intelligence through logical operations, relying on a number of them to achieve their goals and draw their conclusions, the sensitivity of sensory processing is an innate trait that may be more related to the response to both environmental and social stimuli because individuals with sensory processing sensitivity are easily stimulated to external stimuli and they can interpret and understand what is going on around them in the external environment surrounding them. The research showed a number of recommendations: working on rehabilitating and training educational and teaching staff members to use educational programs and different educational activities. It is not enough to use the traditional method of teaching to develop students’ logical intelligence in its five fields so that the educational system can develop the learner’s mental abilities to face various life situations to develop students’ mental abilities and prove their personality and prepare a generation that trusts its mental abilities, emphasizing on the role of the family in enhancing the trait of its children, especially when dealing with others, to enhance external stimuli and provide a sound environment to help its children deal with all different sensory stimuli.